2014
DOI: 10.1155/2014/494956
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ouabain on Human Dendritic Cells Maturation

Abstract: Although known as a Na,K-ATPase inhibitor, several other cellular and systemic actions have been ascribed to the steroid Ouabain (Oua). Particularly in the immune system, our group showed that Ouabain acts on decreasing lymphocyte proliferation, synergizing with glucocorticoids in spontaneous thymocyte apoptosis, and also lessening CD14 expression and blocking CD16 upregulation on human monocytes. However, Ouabain effects on dendritic cells (DCs) were not explored so far. Considering the peculiar plasticity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In the present study, when ouabain was associated with zymosan it significantly decreased the NF- κ B activation observed with zymosan alone. However, similar to a study using dendritic cells [ 16 ] ouabain by itself was capable of increasing NF- κ B activation. Therefore, the decrease in TNF- α and IL-1 β levels observed by us correlates with an inhibitory effect of ouabain on NF- κ B binding activity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the present study, when ouabain was associated with zymosan it significantly decreased the NF- κ B activation observed with zymosan alone. However, similar to a study using dendritic cells [ 16 ] ouabain by itself was capable of increasing NF- κ B activation. Therefore, the decrease in TNF- α and IL-1 β levels observed by us correlates with an inhibitory effect of ouabain on NF- κ B binding activity.…”
Section: Discussionsupporting
confidence: 71%
“…The combination of ouabain plus corticoids produced a synergic effect inducing thymic atrophy in vivo [ 14 ]. Additionally, ouabain was shown to modulate function and cytokine production of monocytes in vitro [ 15 ] and dendritic cells [ 16 ]. Ouabain negatively modulated acute peritoneal inflammatory response induced by Leishmania amazonensis infection in Swiss mice [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of ouabain on DC was also described. Nascimento et al ( 2014 ) demonstrated that ouabain modulates dendritic cells markers and IL-12 production during activation by TNF-α. Additionally, ouabain affects monocyte/macrophage activation (Sowa and Przewłocki, 1997 ; Teixeira and Rumjanek, 2014 ).…”
Section: Ouabain and Immune Systemmentioning
confidence: 99%
“…However, they could clearly demonstrate that ouabain does not influence these cells. Nascimento et al [71] were the first to investigate the action of ouabain (100 nM) on human dendritic cells (DCs). Interestingly, the TNF-induced expression of CD83 and the production of IL-12, two features of DC maturation, were reduced by ouabain, whereas the capability of DCs to activate lymphocytes remained unaltered.…”
Section: Neutrophils Natural Killer Cells and Dendritic Cellsmentioning
confidence: 99%